Thrombospondin-1 Silencing Ameliorates Osteoblastic Differentiation of Aortic Valve Interstitial Cells via Inhibiting Nuclear Factor-κB Pathway - Qing Li; Chengxiang Song; Zisong Wei; Junli Li; Hao Zhou; Shuoding Wang; Hongde Li; Haoran Yang; Qiang Luo; Mao Chen (Cardiovascular Therapeutics)
Conclusions: The present study has shown that TSP-1 silencing could mitigate the development of CAVD by inhibiting NF-κB-mediated inflammation. We propose that targeting TSP-1-mediated NF-κB pathway could provide a potential therapeutic method for treating CAVD.